Harmonization of man-made landscape elements in forestry educational centres with existing forest environment - Jaafar, Syuriaty; Hussein, Mohd Kher; Mohd Yusof, Mohd Johari (Universiti Putra Malaysia Press, 2020)
The Forestry Educational Center is a place where the public can learn more about the forest environment, its importance and what people can do to help protect it. Thus, harmonizing design style to all man-made landscape elements in this site was necessary in order to respect the spectacular scenery and to conserve natural resources, as well as to deliver good education and experience to the user. However, how harmonized the man-made landscape elements are with forest environment in these centers is still in question. Therefore, the aim of this study is to gain people’s perception towards forestry educational centers of man-made landscape elements from the aspect of harmonious designs. An objective of the study is to analyse the user’s educational background on the harmonize design philosophy with regard to the man-made landscape elements of design harmonization towards the forestry educational center. The study is conducted at the Sultan Idris Shah Forestry Education Centre in Selangor, Malaysia, through a questionnaire with photograph surrogates. A total of 150 respondents participated in this study. Moreover, this study revealed that educational background had significantly affected the harmonise design perception that causes differences between education groups. However, results indicated that respondents perceived the present man-made landscape elements of these sites harmonized with the forest environment. As a consequence, harmonizing design approach in this center has enhanced the conservation efforts in protecting the forest destruction from harmful human activities. Indirectly, it helps in promoting the cultural identity of the locals while providing a better educational experience for the user and future generations.